The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000489543
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Role of ARHGAP17 in Colon Cancer Through Wnt/β-Catenin Signaling

Abstract: Background/Aims: A few Rho GTPase activating proteins (RhoGAPs) have been identified as tumor suppressors in a variety of human cancers. ARHGAP17, a member of RhoGAPs, has been reported to be involved in the maintenance of tight junction and epithelial barrier. The present study aimed to explore its expression in colon cancer and the possible function in colonic carcinogenesis. Methods: The mRNA and protein expression was assessed by realtime PCR and immunoblotting, respectively. Cell Counting Kit-8 (CCK-8) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Downregulated ARHGAP10 inhibits tumorigenicity of ovarian cancer cells [ 43 ]. ARHGAP17 plays tumor suppressive role in colon cancer via Wnt/β-Catenin Signaling [ 44 ]. Thus, MUC21, CEACAM1, FUT7, PADI1, PPL, and ARHGAP40 may be associated with the development of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated ARHGAP10 inhibits tumorigenicity of ovarian cancer cells [ 43 ]. ARHGAP17 plays tumor suppressive role in colon cancer via Wnt/β-Catenin Signaling [ 44 ]. Thus, MUC21, CEACAM1, FUT7, PADI1, PPL, and ARHGAP40 may be associated with the development of LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/ β -catenin pathway is intensively studied in multiple cancers, but its role in glioma has only started to emerge [2224]. It has been reported that knockdown of CKIP-1 markedly upregulated the phosphorylated Akt levels at Thr308 and Ser473 and the phosphorylation of GSK-3 β [15].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, one recent study showed that overexpression of Rac1b confers resistance to chemotherapy in colon cancer by activating the NF-pathway [14], which highlights the importance of Rac1 in cancer treatment resistance. We observed that Rac1 activity was downregulated by overexpression of ARHGAP17 in colon cancer cells [15]. Also, mRNA expression of ARHGAP17 was reduced in the samples of colon cancer, and reduced ARHGAP17 expression correlates with poor outcomes of people with colon cancer [15].…”
mentioning
confidence: 81%
“…We observed that Rac1 activity was downregulated by overexpression of ARHGAP17 in colon cancer cells [15]. Also, mRNA expression of ARHGAP17 was reduced in the samples of colon cancer, and reduced ARHGAP17 expression correlates with poor outcomes of people with colon cancer [15]. In contrast, overexpression of ARHGAP17 suppressed tumor cell proliferation, as well as restricted cancer invasion to the lung through Wnt/ -catenin signaling [15], which demonstrated the function of ARHGAP17 in suppressing tumor development as well as metastasis in colon cancer.…”
mentioning
confidence: 83%
See 1 more Smart Citation